2018
DOI: 10.1016/j.arth.2018.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Tibial Implant Decreases Posterior Overhang Rate and Improves Clinical Outcomes: Results of a Prospective, Matched Controlled Study

Abstract: The use of an MTT in TKA did not modify the tibial implant position in the axial plane; however, it decreased implant's posterior overhang and improved functional scores. The clinical improvement was mainly found on pain scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…A result less than 100% corresponded to a non-overflowing implant and a result greater than 100% to an overflowing implant. Medial overhang: distance in millimeters between the medial edge of the tibial component and the medial most border of the proximal tibia directly underneath the implant, as measured by Bizzozero et al [25]. Posterior overhang: distance in millimeters between the posterior edge of the tibial component tray and the posterior most border of the proximal tibia directly underneath the implant (Fig.…”
Section: Radiological Resultsmentioning
confidence: 99%
“…A result less than 100% corresponded to a non-overflowing implant and a result greater than 100% to an overflowing implant. Medial overhang: distance in millimeters between the medial edge of the tibial component and the medial most border of the proximal tibia directly underneath the implant, as measured by Bizzozero et al [25]. Posterior overhang: distance in millimeters between the posterior edge of the tibial component tray and the posterior most border of the proximal tibia directly underneath the implant (Fig.…”
Section: Radiological Resultsmentioning
confidence: 99%
“…It is known that compliance decreases, especially as the tibia becomes smaller [12]. Although gender-specific implants are currently available, their efficacy is also controversial [18]. It should be taken into consideration that we had more female patients than males and they tend to have implants smaller in size.…”
Section: Discussionmentioning
confidence: 99%
“…This is often not possible, partly because current traditional tibial components may not be of ideal shape and often require a compromise between optimal rotation and bone coverage [28,29]. To optimize rotationalcoverage ratios and limit the potential conflicts with the soft tissues, new designs of tibial implants have been developed using large anatomical databases and specific software simulating bone cuts [17]. Thus, morphometric trays have been designed to adapt not only to the morphology of the proximal tibial plateau, but also to its dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies, using positioning simulations of the tray on the basis of computed tomography scans, demonstrated that a morphometric tray allows an optimum rotational positioning, while optimizing the tibial coverage without causing any posterolateral conflict with the soft tissues [31,32]. An in vivo prospective matched controlled study comparing morphometric and symmetric tibial tray conducted by Bizzozero et al [17] using the same design as evaluated in the present study demonstrated that bone coverage (90% vs 88%, P ¼ .07) and rotation (mean difference 0.7 ± 3 ; P ¼ .69) were not different between the 2 groups. But the percentage of patients with a posterior overhang was lower in the morphometric group (2/33 vs 14/33, P ¼ .01, odds ratio 10.3 [2.12-50.24]).…”
Section: Discussionmentioning
confidence: 99%